Performance coaching the handbook for managers, H.R. professionals and coaches Angus I. McLeod - McLeod, Angus (Crown House, 2003)
For anyone involved in business training or coaching, this book is the "bible" of coraching. Dr. McLeod brings together the fundamental of all the best practices in coaching and builds up from this foundation. Fast, accessible and clear written, this volume is comprehensive and rich in real examples from real executives who have achieved real success in real-life situations. Experienced coaches will find important tips and tools to enhance their practice, and novices will find the book a gold-mine of ideas.